How research becomes impact: Librarians helping faculty use scholarly metrics to select journals. Issue 2 (3rd April 2018) - Vinyard, Marc; Colvin, Jaimie Beth
ABSTRACT: Many librarians support faculty with the publishing process, which includes journal selection and evaluating the impact of their scholarly output. While large universities have the resources for entire departments devoted to bibliometrics, the authors of this article give strategies for faculty publishing support at a smaller liberal arts university. The authors created a LibGuide with publishing resources and presented the initiative to several academic divisions. Faculty were surveyed, and the results indicated that the majority of respondents were interested in assessing journal quality and viewed the library as a resource for help with the publishing process.